Analysis of Character Values in The Folklore of The Origin Kretek Industry - Febrianti, Adhelia Putri; Velayali, Istifaiya; Resa Sirotun Hidayah, Eva; Mohammad Kanzunnudin (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to analyze the structure and character values contained in the folklore